Customer Churn Prediction (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
With the rapid advancement of digital systems and related information technologies, there is agrowing tendency in the global economy to develop digital CRM systems. This research uses a real-world study to predict customer churn and recommends the use of PyCaret to improve a customer churn prediction model. Unlike most studies, this work seeks to employ PyCaret Toolkit, an open source machine learning library designed to make executing typical activities in a machine learning project simple.